Theoretical Investigation of Properties of Indoline-2,3-dione-3-oxime Using Chemicalize Software - K. Laxmi (Recent Developments in Chemistry and Biochemistry Research Vol. 6, 2024)
Indoline-2,3-dione-3-oxime (IDOX) (Isatin-3-oxime) is employed as an anticonvulsant and is known for treating various disorders caused by the release of amino acids responsible for anxiety and excitatory behavior. With the application of chemicalize software of Chemaxon the structure and properties of IDOX were studied. In view of the biological importance of IDOX Properties, pka, Isoelectric Point, logP, logD, Solubility, Geometry, and HNMR were determined by using Chemicalize software and the data obtained was interpreted. Information about Structural details of Indoline-2,3-dione-3-oxime (IDOX) and pka value so obtained indicated the presence of one dissociable proton in IDOX.